Geo-environmental investigation: A brief review and a few suggestions for brazilian contaminated sites - Mondelli, Giulliana; Giacheti, Heraldo Luiz [UNESP]; Howie, John A. (My University, 2010)
This paper presents a brief review about site investigation procedures for contaminated sites recommended by Brazilian and Canadian environmental agencies as well as discusses the theme of geo-environmental investigation as applied to Brazilian practice. The main definitions on the theme are reviewed and some guidelines are proposed for conducting a geo-environmental investigation of Brazilian contaminated sites using different site and laboratory investigation techniques based on the presented review and on the experience obtained from the investigation of a solid waste disposal site in the interior of the state of São Paulo, Brazil.
Keywords: Contaminated sites; Environmental geotechnics; MSW disposal site; Regulations; Tropical soils; Contamination; Environmental regulations; Solid wastes; Waste disposal